Handbook of Microbology - Bisen P.S.; Verma Kavitha (New Delhi CBS Publishers and Distributers, 1996)
classification of various fungi and experimental exercies with suitable illustrations and micrometry
viruses cyanobacteria bacillus serratia
Keywords: viruses,bacillus